2005
DOI: 10.1136/hrt.2005.072975
|View full text |Cite
|
Sign up to set email alerts
|

Admission N-terminal pro-brain natriuretic peptide and its interaction with admission troponin T and ST segment resolution for early risk stratification in ST elevation myocardial infarction

Abstract: Objective: To assess the long term prognostic value of N-terminal pro-brain natriuretic peptide (NTproBNP) on admission and its prognostic interaction with both admission troponin T (TnT) concentrations and resolution of ST segment elevation in fibrinolytic treated ST elevation myocardial infarction (STEMI). Design and setting: Substudy of the ASSENT (assessment of the safety and efficacy of a new thrombolytic) -2 and ASSENT-PLUS trials. Patients: NT-proBNP and TnT concentrations were determined on admission i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
5
22
0
1
Order By: Relevance
“…BNP has been valued as a strong and independent prognostic marker in patients with all forms of ACS [11][12][13]16] even when measured upon hospital arrival [15,18,24]. Several studies have also shown that BNP levels rise immediately after spontaneous or stress-induced cardiac ischemia [9,10,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…BNP has been valued as a strong and independent prognostic marker in patients with all forms of ACS [11][12][13]16] even when measured upon hospital arrival [15,18,24]. Several studies have also shown that BNP levels rise immediately after spontaneous or stress-induced cardiac ischemia [9,10,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulus for their release is an increase in left ventricular wall stress. 1) Circulating levels of BNP and NT-proBNP are increased in heart failure, acute coronary syndrome, chronic coronary disease, and atrial fibrillation, 2) and are closely linked to prognosis, [3][4][5][6][7] angiographic procedural complications, 8) and electrophysiological properties in atrial fibrillation.…”
mentioning
confidence: 99%
“…These markers are becoming increasingly accepted by clinicians and laboratorians for the exclusion of HF, a disease with a high morbidity that currently affects 5 ϫ 10 6 people in the US and 10 ϫ 10 6 people in Europe and shows a high prevalence (Ͼ10%) in the elderly population (2,3 ). Recent studies have also indicated that BNP and NTproBNP may be useful as markers in other clinical settings, such as risk assessment in patients with acute coronary syndromes (4,5 ); however, full assessment of several factors, such as the biological variation in BNP (6 -8 ), its limited cardiac specificity, the various circulating forms of proBNP, and the specification of BNP and NT-proBNP assays, will be required to avoid confusion regarding interpreting results for these markers in daily practice (9 ).…”
mentioning
confidence: 99%